Performance of the QUIC Transport Protocol over Geostationary Satellite Links - Jahandar Bonab, Saeid; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (40th International Communications Satellite Systems Conference (ICSSC 2023), 2023)
Traditional transport layer protocols like TCP face limitations in high-latency scenarios, such as geostationary satellite communications. The QUIC protocol is a reliable transport protocol designed for secure communication, low-latency connection setup, and evolvability. This study investigates QUIC's advantages in geostationary satellite environments and evaluates the QUIC implementations picoquic and quiche, both with the congestion control algorithms CUBIC and BBR. NetEm is used to introduce specific path characteristics such as data rate and delay. Docker is used to ensure reproducibility, portability, and environmental consistency, facilitating streamlined setup and configuration across different platforms. Assuming that PEPs are not applicable, results demonstrate that QUIC implementations can outperform TCP in connection establishment time and object download time considering a single flow. Utilizing qlog, a logging format for QUIC, aids in-depth analysis of protocol interactions. qlog files are used to show various metrics: time-offset and retransmissions, pacing rate, congestion window size, bytes in flight, round trip times, throughput, and goodput. Results show that picoquic performs better than quiche regardless of the congestion control algorithm. quiche in combination with BBR shows sub-optimal performance which needs further investigatio